CONTINGENCY FACTORS AND FINANCIAL SUSTAINABILITY OF PHARMACEUTICAL FIRMS IN NIGERIA - Abdulfatai Olanrewaju NURUDEEN; Muhammed Basiru MUSTAPHA; Toheeb A. SHOMORIN (Malete Journal of Accounting and Finance)
Insensitivity to financial sustainability has led some firm to undeserved winding up and significance of the pharmaceutical firms to the health and economic stability of the nation requires a review of the contingency factors that are capable of influencing her financial sustainability attainments. This study therefore examines the effect of contingency factors on the financial sustainability of the pharmaceutical firms in Nigeria. The study adopts a survey research design to ascertain the effect of contingency factors on the financial sustainability of the pharmaceutical firms in Nigeria. The study gathered the data from 234 respondents out of a sample frame size of 330 from 10 largest firms in Nigeria. Multiple regression analysis revealed that leadership style (β = 0.711; p < 0.000); organization culture (β = 0.185; p = 0.000) both has positive and notable effect on the financial sustainability efforts of the pharmaceutical firms in Nigeria. The study concludes that the leadership style and organization culture enhance financial sustainability practices in the firms under the study. The study recommends that Companies’ management should adopt a transactional leadership style and resilient culture in order to achieve more financial sustainability.